1999
DOI: 10.1093/jac/43.suppl_1.67
|View full text |Cite
|
Sign up to set email alerts
|

A trial comparing low-dose, short-course ciprofloxacin and standard 7 day therapy with co-trimoxazole or nitrofurantoin in the treatment of uncomplicated urinary tract infection

Abstract: The therapeutic antitumor effect of clarithromycin (CAM) was examined with the 13762NF mammary adenocarcinoma and F-344 rat system. When CAM treatment at a dosage of 2 mg/kg of body weight orally for 21 days was commenced after inoculation of the tumor, no significant decrease in death rate was observed, although the loss in body weight was less than that in the untreated group. When tumor-bearing (TB) rats were treated with CAM in combination with carboplatin or cyclophosphamide, a significant decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 18 publications
2
43
2
2
Order By: Relevance
“…In these studies, a total of only 14 patients were infected with such organisms. 8,23 There was a similar lack of data for fluoroquinolones 24,25 but relatively more data for TMP-SMX. 8,40,41 More research is needed to better determine the probability of curing UTIs when the causative organism is resistant to the antibiotic used, especially given how increasingly common this scenario is in primary care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, a total of only 14 patients were infected with such organisms. 8,23 There was a similar lack of data for fluoroquinolones 24,25 but relatively more data for TMP-SMX. 8,40,41 More research is needed to better determine the probability of curing UTIs when the causative organism is resistant to the antibiotic used, especially given how increasingly common this scenario is in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, the Figure does not include the probability of vaginal yeast infection, which was calculated for each outcome on the basis of published probabilities. 7,[22][23][24][25] Other potential antibiotic effects or complications (eg, StevensJohnson syndrome) were considered rare and not included in our model, given that a previous investigation of uncomplicated UTIs found that expensive but uncommon events had almost no effect on overall treatment costs. 26 Finally, a model was constructed that compared all 3 treatments: nitrofurantoin, TMP-SMX, and fluoroquinolones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the study drugs was evaluated as follows (11). The patients were considered to be clinically cured when all symptoms had subsided and to have treatment failure when symptoms persisted during therapy or relapsed after the discontinuation of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…For women with acute uncomplicated cystitis who are able to take oral medication, nitrofurantoin (NTF), trimethoprim-sulfamethoxazole (SXT), fosfomycin (FOS) or pivmecillinam (PVM) should be prescribed for a 3-5 day course depending on the agent used. Nitrofurantoin monohydrate/macrocrystals is an appropriate treatment choice due to the minimal resistance [62], efficacy and propensity to cause alteration in the host's flora compared to a 3-day course of SXT [73]. Although SXT is still widely used and recommended for acute cystitis therapy, the caveat is that local resistance rates of uropathogens should not exceed 20%, or if the infecting strain is confirmed to be susceptible [62].…”
Section: Guidelines For Treating Lower Urinary Tract Infectionsmentioning
confidence: 99%